Implicit Voice Theories: Taken-for-Granted Rules of Self-Censorship at Work - Detert, James R.; Edmondson, Amy C. (Academy of Management Journal, 2011)
In four studies, we examine implicit voice theories—taken-for-granted beliefs about when and why speaking up at work is risky or inappropriate. In Study 1, interview data from a large corporation suggest that fine-grained implicit theories underlie reluctance to voice even pro-organizational suggestions. Study 2 survey data address the generalizability of the implicit theories identified in Study 1. Studies 3 and 4 develop survey measures for five such theories, establishing the measures' discriminant validity and incremental predictive validity for workplace silence. Collectively, our results indicate that implicit voice theories are widely held and significantly augment explanation of workplace silence.